Numerical simulation of cavitation erosion on a NACA0015 hydrofoil based on bubble collapse strength. (November 2015) - Hidalgo, V; Luo, X; Escaler, X; Huang, R; Valencia, E
Abstract: The prediction of erosion under unsteady cavitation is crucial to prevent damage in hydraulic machinery. The present investigation deals with the numerical simulation of erosive partial cavitation around a NACA0015 hydrofoil. The study presents the calculation of the bubble collapse strength, Sb, based on the bubble potential energy to identify the surface areas with highest risk of damage. The results are obtained with a numerical scheme assuming homogeneous mixture flow, implicit LES and Zwart cavitation model. The 3D unsteady flow simulation has been solved using OpenFOAM. Python language and OpenFOAM calculator (foamCalcEx) have been used to obtain and represent Sb . The obtained results clearly show the instants of erosive bubble collapse and the affected surface areas.